2018
DOI: 10.1093/europace/euy031
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of delivering high-power short-duration radiofrequency ablation lesions utilizing a novel temperature sensing technology

Abstract: Delivery of high-power short-duration RF energy applications, facilitated by a novel ablation catheter system equipped with advanced TC technology, is feasible, safe, and results in the formation of effective ablation lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…For this reason, all studies advocating HPSD ablation strongly recommend the use of an automatic temperature cutoff. The exact cutoff varies between studies between 50°C and 80°C 8,14,[34][35][36]. Small animal studies have shown safety and efficacy in using high powers between 50 W and 90 W with contact forces of 10-20 g and using irrigated catheters to maintain a catheter tiptissue temperature of less than 55-65°C during lesion formation 8,14,17,37.…”
mentioning
confidence: 99%
“…For this reason, all studies advocating HPSD ablation strongly recommend the use of an automatic temperature cutoff. The exact cutoff varies between studies between 50°C and 80°C 8,14,[34][35][36]. Small animal studies have shown safety and efficacy in using high powers between 50 W and 90 W with contact forces of 10-20 g and using irrigated catheters to maintain a catheter tiptissue temperature of less than 55-65°C during lesion formation 8,14,17,37.…”
mentioning
confidence: 99%
“…[3][4][5] When biophysically compared with conventional RF application, HP-SD energy settings change the relationship of resistive and conductive heating during lesion formation. [3][4][5] When biophysically compared with conventional RF application, HP-SD energy settings change the relationship of resistive and conductive heating during lesion formation.…”
mentioning
confidence: 99%
“…4 Due to anatomical reasons, the assessment of esophageal lesions was rightfully excluded. Therefore, the manufacturer integrated three thermocouples into the distal RF electrode and three thermocouples more proximally.…”
mentioning
confidence: 99%
See 2 more Smart Citations